The Impact of Sports Activities and Teaching Quality on Negative Emotions of Vietnamese Teachers: Mediating Role of Psychological Reliance - Le Thi Ngoc Diep, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The performance of students and educational institutions would be negatively impacted by teachers' negative emotions, requiring an urgent response. To discover a solution to this problem, the present study examines the influence of teaching quality and sports activities on the negative feelings of Vietnam's teachers. In addition, the article investigates the moderating effect of psychological dependency on teaching quality, sports activities, and negative emotions among Vietnam's teachers. Using questionnaires, the study collected data from the selected teachers. The report also used PLS-SEM using smart-PLS to examine the relationship between the study's variables. The data demonstrated a negative relationship between the teaching quality and sports activities and teachers' negative feelings in Vietnam. The results also revealed that psychological dependency strongly mediates the relationship between teaching quality, sports activities, and negative feelings among Vietnam's teachers. The study aids policymakers in formulating strategies to improve teachers' moods through good teaching qualities and athletic activities.